Factors Contributing To Students’ Difficulties In Number Pattern Generalization: A Thematic Qualitative Meta-Analysis Within The Framework Of Early Algebraic Thinking - Azis, Nazwa Wulandari; Muhtadi, Dedi; Sukirwan (Koordinat Jurnal MIPA, 2025)
This study examines students’ difficulties in generalizing number patterns and their multidimensional interactions within early algebraic thinking. A thematic qualitative meta-analysis of 15 Scopus-indexed articles (2019–2024) was conducted under the PRISMA protocol using open coding and thematic clustering (κ = 0.82). Five categories of difficulty were identified: reasoning–generalization (80%), conceptual (73%), procedural–operational (60%), strategic (47%), and didactic (40%). Reasoning–generalization difficulties involved students’ inability to identify relationships or formulate general rules, while conceptual and procedural weaknesses reflected misconceptions of pattern structures and errors in extending sequences. Strategic and didactic challenges were linked to limited problem-solving approaches and insufficient scaffolding. The findings highlight dynamic interactions—especially between conceptual and procedural factors—and emphasize teachers’ mediating role in fostering the transition from arithmetic to algebraic symbolization